Numerical Simulation of Magnetic Dipole Flow Over a Stretching Sheet in the Presence of Non-Uniform Heat Source/Sink - Souayeh, Basma; Yasin, Essam; Alam, Mir Waqas; Hussain, Syed Ghazanfar (Frontiers in Energy Research, 2021)
The main objective of current communication is to present a mathematical model and numerical simulation for momentum and heat transference characteristics of Maxwell nanofluid flow over a stretching sheet. Further, magnetic dipole, non-uniform heat source/sink, and chemical reaction effects are considered. By using well-known similarity transformation, formulated flow equations are modelled into OD equations. Numerical solutions of the governing flow equations are attained by utilizing the shooting method consolidated with the fourth-order Runge-Kutta with shooting system. Graphical results are deliberated and scrutinized for the consequence of different parameters on fluid characteristics. Results reveal that the temperature profile accelerates for diverse values of space dependent parameter, but it shows opposite behaviour for escalated integrity of temperature dependent parameter.